Analisis Laba dan Arus Kas Serta Pengaruhnya Terhadap Kondisi Kesulitan Keuangan Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Aulya Damayanti; Febriyanto; Nani Septiana (Jurnal Manajemen DIVERSIFIKASI, 2026)
This research aims to determine the effect of profits andcash flow on financial difficulties in food and beverage manufacturing companies listed on the Indonesian Stock Exchange. This research uses a quantitative descriptive analysis model. The population in this study were food and bevverage companies for the period 2019 to 2021. The number of samples in this study was 12 food and beverage companies obtained from a purposive sampling technique. The data collection technique uses documentation from financial repots published on the official website of the Indonesia Stock Exchange, namely www.idx.ix. The analysis techniques used are classical assumptions and multiple regression analysis. The results of this research show that profit influences financial difficulties, cash flow influences financial difficulties.